2021
DOI: 10.1182/blood.2020008629
|View full text |Cite
|
Sign up to set email alerts
|

SASH3variants cause a novel form of X-linked combined immunodeficiency with immune dysregulation

Abstract: SAM and SH3 domain-containing 3 (SASH3), also called SH3-containing Lymphocyte Protein (SLY1) is a putative adaptor protein that is postulated to play an important role in the organization of signaling complexes and propagation of signal transduction cascades in lymphocytes. The SASH3 gene is located on the X-chromosome. Here, we identified three novel SASH3 deleterious variants in four unrelated male patients with a history of combined immunodeficiency and immune dysregulation manifesting as recurrent sinopul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…19,20 One patient with SASH3 deficiency failed to make anti-S IgG after 2 doses of an mRNA vaccine, which is consistent with the disease phenotype. 21 In the immunodeficient cohort, a CD3 1 cell count of less than 1000 cells/mL at baseline (before vaccination) was associated with lower anti-S IgG levels at the second time point after immunization (Fig 2, A). Furthermore, patients with CD19 1 cell counts of less than 100 cells/mL at baseline had a significantly lower GM of anti-S IgG levels than did patients with a CD19 1 cell count of 100 cells/mL or higher both after the first dose (60,621 LU Most patients receiving immunoglobulin replacement therapy developed protective anti-S antibody titers, and the only 2 patients (patients 10 and 75 [see Table E1]) who tested positive for anti-N antibodies after immunization had a history of SARS-CoV-2 infection, which is consistent with the fact that most currently available immunoglobulin preparations are not derived from SARS-CoV-2-exposed donors (Fig 3, A).…”
Section: Resultsmentioning
confidence: 88%
“…19,20 One patient with SASH3 deficiency failed to make anti-S IgG after 2 doses of an mRNA vaccine, which is consistent with the disease phenotype. 21 In the immunodeficient cohort, a CD3 1 cell count of less than 1000 cells/mL at baseline (before vaccination) was associated with lower anti-S IgG levels at the second time point after immunization (Fig 2, A). Furthermore, patients with CD19 1 cell counts of less than 100 cells/mL at baseline had a significantly lower GM of anti-S IgG levels than did patients with a CD19 1 cell count of 100 cells/mL or higher both after the first dose (60,621 LU Most patients receiving immunoglobulin replacement therapy developed protective anti-S antibody titers, and the only 2 patients (patients 10 and 75 [see Table E1]) who tested positive for anti-N antibodies after immunization had a history of SARS-CoV-2 infection, which is consistent with the fact that most currently available immunoglobulin preparations are not derived from SARS-CoV-2-exposed donors (Fig 3, A).…”
Section: Resultsmentioning
confidence: 88%
“…Novel gene defects have been found for most categories of IEI, including novel causes of: Combined immunodeficiencies ( LCP2 (SLP76) [ 12 ], PAX1 [ 13 , 14 ], ITPKB [ 15 ]; SASH3 [ 16 , 17 ], MAN2B2 [ 18 ], COPG1 [ 19 ], IKZF2 [ 20 – 23 ], CHUK [ 24 ], IKZF3 [ 25 , 26 ], CRACR2A [ 27 ], CD28 [ 28 ]) (Table 1 ; Supplementary Table 1 ); Combined immunodeficiencies with syndromic features ( MCM10 [ 29 , 30 ], IL6ST [ 31 – 33 ], DIAPH1 [ 34 ]) (Table 2 ; Supplementary Table 1 ); B cell deficiencies, agammaglobulinemia, or hypogammaglobulinemia ( FNIP1 [ 35 , 36 ], SP1I [ 37 ] , PIK3CG [ 38 , 39 ], POU2AF1 [ 40 ], CTNNBL1 [ 41 ], TNSRSF13 [ 42 ]) (Table 3 ; Supplementary Table 1 ); Immune dysregulation ( RHOG [ 43 ], SOCS1 [ 44 – 46 ], PDCD1 [ 47 ], ELF4 [ 48 , 49 ], TET2 [ 50 ], CEBPE [ 51 ], IKZF1 GOF [ 52 ]) (Table 4 ; Supplementary Table 1 ) neutropenia CXCR2 [ 53 ...…”
Section: Novel Inborn Errors Of Immunitymentioning
confidence: 99%
“…There can be clinical overlap between some genes listed here and those listed in Table 7 Total number of mutant genes: 66. New inborn errors of immunity: 8 ( SLP76 [ 12 ], PAX1 [ 13 , 14 ], ITPKB [ 15 ]; SASH3 [ 16 , 17 ], MAN2B2 [ 18 ], COPG1 [ 19 ], IKZF2 [ 20 – 23 ], CHUK [ 24 ]) SCID severe combined immunodeficiency, CID combined immunodeficiency, EBV Epstein-Barr virus, MHC major histocompatibility complex, HPV human papillomavirus, Treg T regulatory cell, XL X-linked inheritance, AR autosomal recessive inheritance, AD autosomal dominant inheritance, LOF loss-of-function, GOF gain-of-function, FTT failure to thrive…”
Section: Novel Inborn Errors Of Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SASH3 functions as an adaptor protein in lymphocytes (40)(41)(42). Recent study showed that SASH3 is important for T-cell proliferation, activation and cell survival, and lack or mutation of SASH3 could lead to a new type disease of human X-linked combined immunodeficiency, which was manifested as CD4 + T-cell lymphopenia, decreased Tcell proliferation, cell cycle progression, and increased T-cell apoptosis in response to mitogens (43). However, the precise function of SASH3 remains unknown.…”
Section: Discussionmentioning
confidence: 99%